Pengaruh Dividend Per Share, Dividend Payout Ratio dan Net Profit Margin terhadap Harga Saham pada Perusahaan LQ45 yang Terdaftar di BEI Tahun 2019-2023 - Nur Alfriani Handayani; Cris Kuntadi; Rachmat Pramukty (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This research uses a quantitative approach to analyze the effect of dividend per share, dividend payout ratio, and net profit margin on stock prices of LQ45 companies listed on the Indonesia Stock Exchange. The population of this study consists of 45 companies included in the LQ45 index during the 2019-2023 period, with a sample size of 125 data points. The results indicate that dividend per share (DPS) has a positive effect on stock prices, while the dividend payout ratio (DPR) and net profit margin (NPM) have a negative effect on stock prices.